Attaining sinus rhythm mediates improved outcome with early rhythm control therapy of atrial fibrillation: the EAST-AFNET 4 trial . (29th August 2022) - Eckardt, Lars; Sehner, Susanne; Suling, Anna; Borof, Katrin; Breithardt, Guenter; Crijns, Harry; Goette, Andreas; Wegscheider, Karl; Zapf, Antonia; Camm, John; Metzner, Andreas; Kirchhof, Paulus
Abstract: Aims: A strategy of systematic, early rhythm control (ERC) improves cardiovascular outcomes in patients with atrial fibrillation (AF). It is not known how this outcome-reducing effect is mediated. Methods and results: Using the Early treatment of Atrial Fibrillation for Stroke prevention Trial (EAST—AFNET 4) data set, potential mediators of the effect of ERC were identified in the total study population at 12-month follow up and further interrogated by use of a four-way decomposition of the treatment effect in an exponential model predicting future primary outcome events. Fourteen potential mediators of ERC were identified at the 12-month visit. Of these, sinus rhythm at 12 months explained 81% of the treatment effect of ERC compared with usual care during the remainder of follow up (4.1 years). In patients not in sinus rhythm at 12 months, ERC did not reduce future cardiovascular outcomes (hazard ratio 0.94, 95% confidence interval 0.65–1.67). Inclusion of AF recurrence in the model only explained 31% of the treatment effect, and inclusion of systolic blood pressure at 12 months only 10%. There was no difference in outcomes in patients who underwent AF ablation compared with those who did not undergo AF ablation. Conclusion: The effectiveness of early rhythm control is mediated by the presence of sinus rhythm at 12 months in the EAST-AFNET 4 trial. Clinicians implementing ERC should aim for rapid and sustained restoration of sinus rhythm in patients with recently diagnosed AF and cardiovascular comorbidities. Structured Graphical Abstract: Structured graphical abstract The EAST-AFNET 4 trial data set was analysed for potential mediators of the outcome-reducing effect of the early rhythm control strategy in the trial. All factors that were different between randomized groups at the 12-month visit were considered. Attaining sinus rhythm explained most of the treatment effect in a landmark analysis considering the remaining 4.1 follow-up years. In conclusion, clinicians aiming to implement early rhythm control should try to attain sinus rhythm.